Improving The Students’ Interest In English Learning Process By Using Canva Application At The Sixth Female Grade Of Al-Jauhar Islamic Boarding School - Khairunnisa, Alfia (Unit Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Agama Islam Hubbulwathan, Duri, Indonesia, 2024)
This aim of this study was Improving The Students’ Interest in English Learning Process by Using Canva Application at The Sixth Grade of Al-Jauhar Islamic Boarding School, this kind of study was Classroom Action Research, where this study was conducted from activity of students in a classroom, while the the subject was the students of the sixth female grade at aljauhar Islamic boarding school, the researcher are used cluster random sampling. There were 20 sample from 52 population, that was observed is the students interest in the English learning process in the classroom by using Canva Application, the technique of data analysing was by using Questionnaire and observation sheet, and documentation, research result in this study is Students' interest in the English language learning process using the Canva application has increased in each cycle, after being applied using the Canva application, the initial condition before using the canva application, students' interest in learning English is still relatively low, namely 40%, in cycle 1 after using the canva application gets a score of 60% and in cycle II the cycle score increases to 100%, it can also be seen from the results of student practice in each which has increased, in cycle 1 the percentage of completeness is 40%, in cycle II the percentage of completeness increases to 70%, this can be a positive impact for students in learning English by using the canva application.